2014
DOI: 10.1007/s11060-014-1394-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation and bevacizumab in recurrent high-grade glioma: an effective treatment option

Abstract: Re-irradiation has been shown to be a meaningful option for recurrent high-grade glioma (HGG) patients. Furthermore, bevacizumab exerts certain activity in combination with chemotherapy/as monotherapy and was safely tested in combination with radiotherapy in several previous studies. To our knowledge, this is the largest cohort of patients treated with both re-irradiation and bevacizumab to date. After receiving standard radiotherapy (with or without TMZ) patients with recurrent HGG were treated with bevacizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…Several studies evaluated the combination of bevacizumab with re-irradiation with the hypothesis that vascular normalization results in improved oxygenation of tumor tissue and thereby increases the effect of radiation. With heterogeneous cohorts of WHO grade III (n=6, n=14, n=12) and glioblastomas (n=8, n=43, n=42) treated with re-irradiation with and without bevacizumab a higher median PFS (5.7 vs. 3.7, 5.6 vs. 2.5, and 6 vs. 4 months) and higher median OS (8.3 vs. 14.3, 8.6 vs. 5.7, 11 vs 8.3 months) were reached in 2 of 3 retrospective studies in the bevacizumab cohort [40][41][42]. In the study of Minniti and colleagues the non-bevacizumab group received fotemustine.…”
Section: Repeat Radiotherapymentioning
confidence: 98%
“…Several studies evaluated the combination of bevacizumab with re-irradiation with the hypothesis that vascular normalization results in improved oxygenation of tumor tissue and thereby increases the effect of radiation. With heterogeneous cohorts of WHO grade III (n=6, n=14, n=12) and glioblastomas (n=8, n=43, n=42) treated with re-irradiation with and without bevacizumab a higher median PFS (5.7 vs. 3.7, 5.6 vs. 2.5, and 6 vs. 4 months) and higher median OS (8.3 vs. 14.3, 8.6 vs. 5.7, 11 vs 8.3 months) were reached in 2 of 3 retrospective studies in the bevacizumab cohort [40][41][42]. In the study of Minniti and colleagues the non-bevacizumab group received fotemustine.…”
Section: Repeat Radiotherapymentioning
confidence: 98%
“…Overall and progressionfree survival were significantly better in the bevacizumab cohort. Combined with conventionally fractionated reirradiation (median dose 36 Gy), median survival was 8.6 months (79). Compared with patients who did not receive bevacizumab (n=44), the patients who received bevacizumab after radiosurgery (n=11) in a case-control study had significantly prolonged progression-free survival (15 months vs. 7 months, p=0.035) and overall survival (18 months vs. 12 months, p=0.005) and were less likely to develop an adverse radiation effect (9 vs. 46%, p=0.037).…”
Section: Combination Treatmentmentioning
confidence: 99%
“…Several trials have been published with results comparable to microsurgical reresection; reported PRS was in the range of 6-12 months. 18 The major limiting factors of percutaneous re-irradiation are tumor/treatment volume, applied total dose, as well as the time interval to initial radiotherapy. The recommended time interval between initial and re-irradiation should not fall short of 6 months.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Flieger et al showed that the concomitant administration of bevacizumab (BEV) in patients undergoing re-irradiation for HGGs significantly improved PFS. 18 The armamentarium of systemic approaches for treatment of recurrent HGGs mainly consists of rechallenge regimens comprising established alkylating agents such nitrosoureas (e.g. carmustine, lomustine, imustine) and TMZ.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%